2008
DOI: 10.1186/1471-2474-9-55
|View full text |Cite
|
Sign up to set email alerts
|

Cutpoints for mild, moderate and severe pain in patients with osteoarthritis of the hip or knee ready for joint replacement surgery

Abstract: Background: Cutpoints (CPs) for mild, moderate and severe pain are established and used primarily in cancer pain. In this study, we wanted to determine the optimal CPs for mild, moderate, and severe pain in joint replacement surgery candidates with osteoarthritis (OA) of the hip or knee, and to validate the different CPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 25 publications
5
103
0
2
Order By: Relevance
“…The patients with hip OA in this study were categorized as having mild to moderate hip pain on the WOMAC pain subscale (minimum-maximum, 5.2-59.4). 27 Despite the mild to moderate pain reported by the patients with hip OA, they had significantly lower scores on the physical functioning and role limitations physical subscales of the SF-36, compared to the matched control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients with hip OA in this study were categorized as having mild to moderate hip pain on the WOMAC pain subscale (minimum-maximum, 5.2-59.4). 27 Despite the mild to moderate pain reported by the patients with hip OA, they had significantly lower scores on the physical functioning and role limitations physical subscales of the SF-36, compared to the matched control group.…”
Section: Discussionmentioning
confidence: 99%
“…To categorize the patient's pain level we used the WOMAC pain subscale (10 to 40, mild pain; greater than 40 to 60, moderate pain; greater than 60 to 100, severe pain). 27 Psychometric studies have shown moderate to high validity and…”
Section: Patients Tmentioning
confidence: 99%
“…These items have substantial research support to validate their discriminatory and prognostic importance. (13,19,31,38,39,43,(47)(48)(49)53,54,(57)(58)(59)(60)(66)(67)(68)73,76,80,82,85,86,97,106,108,110,(112)(113)(114)(115)(116)122) This stratification of cLBP by impact would be appropriate whether or not there appears to be contributory degenerative pathoanatomy. Even when pathoanatomic conditions are thought to contribute to symptoms and dysfunction, they often coexist and overlap, and sometimes fail to respond to specific interventions.…”
Section: How Often Has Low-back Pain Been An Ongoing Problem For You mentioning
confidence: 99%
“…Classification and Prognosis: The Task Force did not undertake a systematic literature review, but considered previous work on back pain taxonomy, (4,6,15,24,33,34,44,52,56,74,79,83,101,104,105,117) prognostic classification, (13,19,31,38,39,43,48,49,53,54,(57)(58)(59)(60)(66)(67)(68)73,76,80,82,85,86,97,106,108,110,(112)(113)(114)(115)(116)122) pain and psychosocial measures, (12,31,...…”
Section: Review Of Existing Literature On Back Painmentioning
confidence: 99%
“…Originally, the BPI was developed to evaluate cancer pain, but has been shown to be valid and reliable for chronic non-cancer pain. 66 For mild OA, the cut points were a score of 0-4, for moderate OA, the cut points were a score of > 4 to 7, and for severe OA, the cut points were > 7 to 10. 66 Prior to launch, the survey was pilot tested among staff and faculty at the University of Tennessee Health Science Center.…”
Section: Survey Instrumentationmentioning
confidence: 99%